Research Trends of Acupuncture Therapy on Chronic Pelvic Pain Syndrome from 2000 to 2022: A Bibliometric Analysis - Hu J; Xiao Y; Jiang G; Hu X (Journal of Pain Research, 2023)
Jinyu Hu,1,* Yuanyi Xiao,1,* Guilin Jiang,2 Xiaorong Hu2 1School of Graduate and Clinical Medicine, Jiangxi University of Chinese Medicine, Nanchang City, People’s Republic of China; 2Department of Clinical Medicine, The Affiliated Hospital of Jiangxi University of Chinese Medicine, Nanchang City, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaorong Hu; Guilin Jiang, The Affiliated Hospital of Jiangxi University of Chinese Medicine, Nanchang City, Jiangxi Province, People’s Republic of China, Email 414496410@qq.com; j1333070957788@163.comBackground: Acupuncture is considered an important means of analgesic, which has been widely used in chronic pelvic pain syndrome (CPPS) management and treatment in recent years, published a large number of related documents. However, the relevant literature in this field has not been summarized and quantitatively analyzed. Therefore, this study aims to analyze the hotspots and predicting future research trends of acupuncture on pelvic pain syndrome.Methods: Search for the relevant publications of the web of science database from 2000 to 2022 about the treatment of acupuncture on chronic pelvic pain syndrome. The Citespace software and VosViewer software are used to analyze the visualization of the countries, institutions, authors, keywords and references and references in the literature.Results: A total of 173 publications were included. The annual number of essays gradually showed an overall growth trend over time. Medicine magazine is the most published journal in this field. J UROLOGY and Acupunct Med are the most cited journals and the most influential magazines; The most active and influential country is China, and the most produced institutions are Beijing University of Chinese Medicine; The most produced authors are Liu Zhishun. The most cited and most influential authors are Nickel JC and Armour M; keywords and cited reference analysis show that the quality of life, mechanism research, alternative medicine and electro-acupuncture will be the scientific hotspot of acupuncture treatment for chronic pelvic pain syndrome.Conclusion: This study shows that acupuncture on CPPS is increasingly valued and recognized. The future research hotspots will focus on the effects and mechanisms. In the future, more high-quality animal basic research will be required to explore the exact mechanism of acupuncture on CPPS. In addition, different parameters of acupuncture such as electric-acupuncture, stimulating frequency, duration and strength are also the focus of future research. More clinical trials are required to verify its safety and effectiveness.Keywords: acupuncture, chronic pelvic pain syndrome, bibliometrics, CiteSpace